Stability in reproductive timing and habitat usage of Chinook salmon across six years of varying environmental conditions and abundance. (21st March 2020) - Peterson, Matthew L.; Lee, Dana J.; Montgomery, John; Hellmair, Michael; Fuller, Andrea; Demko, Doug
Abstract: The spatial and temporal distribution of spawning activity by autumn‐run Chinook salmon Oncorhynchus tshawytscha (Walbaum) was examined across multiple years. The study period included two years of extreme drought conditions when water temperatures in the spawning reach of the Stanislaus River were considered sub‐optimal for spawning and egg incubation. Despite varying levels of superimposition, redd counts and densities remained stable and positively associated with river location, indicating that superimposition may be driven by habitat preference rather than the absence of suitable spawning locations. Spawning occurred slightly later during drought years (6–10 days later compared with wetter years). This delay was attributable to deferred migration instead of deferred spawning, and the majority of redds were constructed at water temperatures exceeding the optimal temperature range. As a consequence, estimates of juvenile production during 2014 and 2015 were among the lowest on record. These findings may be related in part to the high hatchery contribution to the population, above‐average temperatures during spawning and incubation, and superimposition rates. Management recommendations include adequate cold‐water storage in the upstream reservoir, refined spawning habitat restoration techniques in the light of superimposition rates and, on a broader system scale, actions that reduce the amount of stray hatchery Chinook salmon.